Neutrophilic Alveolitis and High Serum Pro-Brain Natriuretic Peptide Level may be Indicators of Pulmonary Functional Impairment in Connective Tissue Disorders - Serap UNCULU,; Özlem Erçen DİKEN,; Aydın ÇİLEDAĞ,; Aydan İKİNCİOĞULLARI,; Demet KARNAK,; Oya KAYACAN,; Murat TURGAY, (Archives of Rheumatology, 2016)
Objectives: This study aims to assess the role of several diagnostic tests and tools, immune markers, and the association between serum pro-brain natriuretic peptide levels and other parameters in patients with collagen tissue disorders with pulmonary involvement. Patients and methods: In this prospective study, 62 patients (17 males, 45 females; mean age 58.1±13.6 years; range 24 to 87 years) with pulmonary involvement of connective tissue disorders were evaluated using several functional parameters (six-minute walking test, serum pro-brain natriuretic peptide, echocardiographic measurement of the pulmonary pressure, respiratory functional parameters, and blood pressure measurement), bronchoalveolar lavage differential cytology and/or flow cytometric analysis. Results: Duration of disease was 7.6 years. Diagnoses included rheumatoid arthritis (38.7%), scleroderma (38.7%), primary Sjögren's syndrome (16.1%), mixed collagen tissue disorder (4.8%), and systemic lupus erythematosus (1.6%). Pulmonary hypertension was present in 38.7% of the patients with the highest incidence of rheumatoid arthritis showing reduced respiratory functions, partial oxygen pressure, and six-minute walk distance, as well as increased serum pro-brain natriuretic peptide and neutrophilic alveolitis. Conclusion: High serum pro-brain natriuretic peptide levels and neutrophilic alveolitis may provide diagnostic clues for a possible diagnosis of pulmonary hypertension and impaired respiratory functions.